Pengaruh Persepsi Kegunaan, Persepsi Kemudahan, Persepsi Resiko Terhadap Keputusan Penggunaan BNI Mobile Banking (Studi Kasus pada Nasabah BNI Kec. Lowokwaru) - Kukuh, Kukuh; Basalamah, Muhammad Ridwan; Wahono, Budi (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This study was conducted to determine the effect of perceived usefulness, perceived ease and perceived risk on the decision to use BNI Mobile Banking (case study of BNI CI customers in Lowokwaru District) This research method uses a quantitative method using a non-probability sampling technique while the data used uses primary data with data collection using a Likert-scale questionnaire distributed in the form of a google form. Sampling in this study used the Malhotra formula and was found to be 80 respondents. Simultaneously, it is known that perceived usefulness, perceived ease and perceived risk have a significant effect on the decision to use BNI Mobile Banking in the Lowokwaru community. While partially the perception of risk has an insignificant effect. This data analysis was carried out using the assistance of IBM SPSS Statistics 25. Keywords: Perceived Usefulness, Perceived Ease Of Use, Perceived Risk